The modification of individual factors on association between serum 25(OH)D and incident type 2 diabetes: Results from a prospective cohort study - Hu, Zhiyong; Zhi, Xueyuan; Ma, Yiming; Li, Jiafu; Wang, Jinxiu; Zhu, Jianliang; Li, Bingyan; Zhang, Zengli (Frontiers in Nutrition, 2022)
Several epidemiological studies have suggested an association between low vitamin D status and increased risk for type 2 diabetes (T2D). This study aimed to explore the dose-response relationship of serum 25-hydroxyvitamin D [25(OH)D] concentrations with incident T2D and the interaction between serum 25(OH)D with individual factors on T2D risk. A total of 1926 adults without diabetes (mean age: 52.08±13.82 years; 42% men) were prospectively followed for 36 months. Cox proportional hazards model and restricted cubic spline analysis were performed to assess the association and dose-response relationship between serum 25(OH)D and T2D incidence. Both additive and multiplicative interactions were calculated between serum 25(OH)D and individual factors. The net reclassification index (NRI) was used to evaluate the improvement of risk prediction of T2D by adding serum 25(OH)D to traditional risk factors. There were 114 new T2D cases over a mean follow-up of 36 months. Serum 25(OH)D was not associated with T2D incidence, and no significant dose-response relationship was found in the total population. However, stratified analyses suggested a nonlinear inverse relationship among individuals with baseline fasting plasma glucose (FPG) < 5.6 mmol/L (Poverall=0.061, Pnonlinear=0.048). And a significant multiplicative interaction was observed between serum 25(OH)D and FPG on T2D risk (P=0.005). In addition, we found a significant additive interaction of low serum 25(OH)D with older age (RERI=0.897, 95% CI: 0.080-1.714; AP=0.468, 95% CI:0.054-0.881), male (AP=0.441, 95% CI: 0.010-0.871), and insufficient physical activity (RERI=0.875, 95% CI: 0.204-1.545; AP=0.575, 95% CI: 0.039-1.111) on T2D risk. Significant additive interactions were also observed between vitamin D deficiency/insufficiency with male, overweight/obesity, and insufficient physical activity on T2D risk. Moreover, adding low serum 25(OH)D to a model containing established risk factors yielded significant improvements in the risk reclassification of T2D (NRI=0.205, 95% CI: 0.019-0.391). Our results indicated a nonlinear relationship of serum 25(OH)D concentrations with T2D risk among individuals with normal FPG and additive interactions of serum 25(OH)D with gender, overweight/obesity, and physical activity on T2D risk, suggesting the importance of outdoor exercise.